Single-step synthesis of ZnO/TiO2 nanocomposites by microwave radiation and their photocatalytic activities - Jirapong Arin (2018)
Zn(NO 3 ) 2 ·6H 2 O and C 4 K 2 O 9 Ti·2H 2 O with 1:1 and 2:1 M ratios of Zn:Ti in solutions at the pH 10 were irradiated by 180 W microwave radiation for 40 min to form ZnO/TiO 2 nanocomposites, new candidates for photodegradation and photoreduction in UV light with very high efficiency. Upon processing the nanocomposites at high temperatures, pure Zn 2 TiO 4 nanocrystals were synthesized only by the 700 °C and 3 h calcination of the 2:1 M ratio Zn:Ti precursors. © 2013 Elsevier B.V.